The rise and fall of Neotropical biodiversity - Antonelli, Alexandre (Botanical journal of the Linnean Society, 2022)
Abstract The exceptional levels of biodiversity found today in the American tropics are the outcome of tens of millions of years of evolution, shaped by the tumultuous geological history of the region, its heterogeneous habitats, climate change, ecological interactions and, in recent millennia, human influence. Although our understanding of diversity patterns and their underlying processes grows steadily in breadth and depth, Neotropical biodiversity is rapidly breaking down. Here, I contrast the long-term evolution of Neotropical biodiversity with its recent and rapid deterioration due to anthropogenic factors. I consider the impacts of the early arrival of humans to the region and the modern intensification of land-use change (primarily driven by agriculture) and other drivers of biodiversity loss, such as direct exploitation, invasive species and climate change. Together, these threats have led to 33% of all Neotropical species for which sufficient data are available being currently threatened with extinction. I outline emerging opportunities for conservation and restoration under the post-2020 Global Biodiversity Framework and call for urgent action from the biodiversity community, for the benefit of people and nature.